Preoperative pembrolizumab combined with chemoradiotherapy for oesophageal squamous cell carcinoma (PALACE-1). (February 2021) - Li, Chengqiang; Zhao, Shengguang; Zheng, Yuyan; Han, Yichao; Chen, Xiaoyan; Cheng, Zenghui; Wu, Yuquan; Feng, Xijia; Qi, Weixiang; Chen, Kai; Xiang, Jie; Li, Jian; et al.
Abstract: Background: To investigate the safety and activity of preoperative pembrolizumab combined with chemoradiotherapy for resectable oesophageal squamous cell carcinoma (ESCC) (ClinicalTrials.gov number, NCT03792347). Methods: Twenty resectable ESCC patients, regardless of programmed death ligand-1 status, received preoperative pembrolizumab with concurrent chemoradiotherapy (PPCT). Preoperative therapy includes carboplatin (area under the curve of 2 mg per milliliter per minute, once a week for 5 weeks), paclitaxel (50 mg/m 2, once a week for 5 weeks), radiotherapy (23 fractions of 1.8 Gy, 5 fraction a week) and pembrolizumab (2 mg/kg) on days 1 and 22. Within 4–6 weeks after preoperative therapy, patients underwent surgery. The primary end-point was safety and secondary outcome measures were feasibility, pathologic complete response (pCR) rate and radiographic response. Immune signature of CD8 + T cells was evaluated in surgical specimens using immunohistochemistry and immunofluorescence. Results: All patients have received PPCT successfully, except one patient who missed the last dose of chemotherapy due to leukopenia. Grade III and higher adverse events (AEs) were observed in 13 patients (13/20, 65%), and one patient had a grade V AE. The most frequent grade III AE was lymphopenia (12/13, 92%). Eighteen patients underwent surgery within 4–9 weeks after PPCT and the pCR rate was 55.6% (10/18). The percentage of transcription factor 1 positive cells was significantly higher in specimens of pCR group than those of non-pCR group ( p value = 0.010). Conclusions: PPCT was safe, did not delay surgery, and induced a pCR in 55.6% of resected tumours. A phase II multicentre study is undergoing for further confirmation of efficacy (NCT04435197). Highlights: We present the safety of preoperative immuno-chemo-radiotherapy for oesophageal cancer. The pathologic complete response rate was 55.6%. This work provided basis for a phase II study to further confirm the efficacy.